The Block Bootstrap for Parameter Estimation Error In Recursive Estimation Schemes, With Applications to Predictive Evaluation - Norman R. Swanson; Valentina Corradi (Rutgers University, Department of Economics, 2003)
n.a.
Keywords: C51; C22; 330; block bootstrap; recursive estimation scheme; nonlinear causality; parameter estimation error; predictive density; Bootstrap-Verfahren; Schätztheorie; Kausalanalyse; Prognoseverfahren; Theorie